Iginuhit ng tadhana - De Villa, Jose.; Conde, Conrado; Torres, Mar S. ([Manila 777 Films], 1965)
Iginuhit ng tadhana chronicles the rise of one of the most powerful and controversial leaders the Philippines ever had Ferdinand E. Marcos. The movie shows details of his life from the time he was born, to his days as a youth in his hometown, growing up in a political family, to his incarceration for allegations of murdering his father's political rival, up to his highly publicized whirlwind marriage to Imelda Marcos.
DVD
Gloria Romero, Luis Gonzales, Rosa Mia, Dindo Fernando, Vilma Santos.
Keywords: Marcos, Ferdinand Edralin -- 1917-1986.; Feature films